Effects of ABCA1 Gene Polymorphisms on Lipid Profile in a Scottish Population - A Pasdar; AM Cumming; D St. Clair; MJ MacLeod (Tehran University of Medical Sciences, 2005)
The ATP Binding Cassette Transporter (ABCA1) is a protein involved in lipid metabolism. Common polymorphisms in this gene could affect High Density Lipoprotein Cholesterol (HDL-C), triglyceride and Apolipoprotein A1 (apoA1) levels and thus the risk of atherosclerotic diseases. To assess the effects of different ABCA1 genotypes on lipid profile, a cohort of 181 healthy Scottish individuals with complete lipid profile data (adjusted for age, sex, BMI and smoking, drinking habits) along with another cohort of 194 healthy control subjects from Aberdeen with main lipid profile data were recruited. We studied four common polymorphisms in ABCA1 gene at different positions, G158A (Leu/Leu), G219A (Arg/Lys), G316A (Gly/Gly) and A1587G (Lys/Arg). Genotyping assays were based on Dynamic Allele Specific Hybridisation (DASH). Results: No significant differences were found in VLDL/TG, VLDL/Cholesterol, LDL, HDL2 and HDL3 concentrations in females or males between different genotypes in the Scottish and Aberdeen cohorts. However, in females with different A1587G genotypes in Scottish cohort, IDL was higher in "AA" genotype (table1). It was also higher in females with G219A "GG" genotype (table2). Males with G316A "GA" genotype also had a higher level of HDL (Mean HDL: "GG", 53.27; "GA", 63: P= 0.032). In conclusion, only A1587G "AA" and G219A "GG" genotypes may influence IDL in females. Females with G219A "GG" and those with "AA" genotypes might also have a higher total cholesterol (P=0.036) and a lower total HDL (P= 0.049) respectively.